Inovasi Model Pembelajaran Problem Based Learning Untuk Berpikir Kritis Pada Mata Pelajaran Matematika Di Sd Negeri Birowo 03 Binangun Blitar - Kasturi, Kasturi; Sukoriyanto, Sukoriyanto; Dewi, Radeni Sukma Indra (Universitas Nahdlatul Ulama Blitar, 2024)
The focus of this article is to identify PBL-based mathematics learning innovations and PBL-based mathematics learning outcomes. The method used is qualitative and the type is a case study. Data collection techniques were carried out using interviews, observation, and documentation and data analysis was carried out in three activity streams that occurred simultaneously in the data collection process, namely: data condensation, data presentation, and conclusion drawing/verification. The research results stated that the stages of PBL-based mathematics learning consisted of three main steps, namely the teacher providing an explanation of the material first before presenting the problem, the teacher giving work papers, and students being directed to complete the work papers in groups. This PBL model indicates that teachers have good managerial skills in the learning process. The results of mathematics learning using the PBL method indicate the delivery of material during the learning process, and students' social skills during learning. The PBL method has an important meaning in seeing the success of learning and education. Both specifically in mathematics and all other subjects. Considering learning outcomes can be used to prepare learning evaluations.